On right (left) θ-centralizers on Banach algebras - Ghazal Moradkhani; Neda Ghoreishi (Journal of Hyperstructures, 2023)
Let A be a Banach algebra with unity 1, and θ : A → A be an continuous automorphism. In this paper we characterizea continuous linear map T : A → A which satisfies one of the following conditions:a, b ∈ A, ab = w =⇒ θ(a)T(b) = T(w),a, b ∈ A, ab = w =⇒ T(a)θ(b) = T(w),or a, b ∈ A, ab = w =⇒ θ(a)T(b) = T(a)θ(b) = T(w) , where w ≠ 0 is a left (right) separating point of A.